PERSEPSI PEMBELI GENTONGS.SECOND TENTANG KUALITAS PELAYANAN PENJUAL DALAM EVENT SESI TUKU - Bayu Sejati, Mahendra; Hindra H, Nurnawati; Maserona S, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The quality of gentongs.second service is shown through consumer statements or messages that are associated with buyer perception before making a product purchase transaction and to find out this, it is necessary to research buyers in gentongs.second itself. This research was conducted to find out how gentongs.second buyers perceive the quality of seller service. The theory used in this study is the theory of perception according to Ramadhani, the theory of service quality according to Wyckof. This research is descriptive with qualitative methods. The results of this study concluded that the perception of gentongs.second buyers states that the quality of seller service is good and meets buyer expectations, where it is conveyed through interviews such as good and quality product perceptions, affordable and relatively cheap product prices, easy to understand information delivery, smooth language and being polite in building communication between buyers and sellers, and fast and responsive service. KEYWORD: Gentongs.second, Buyer Perception, Quality Service